Financial Performance of Commercial Banks in Afghanistan - Haidary, Qais; Abbey, Boris (International Journal of Economics and Financial Issues, 2018)
Banks play a vital role in a country's economic system but they are only able to operate on a going concern basis if they are managed effectively and efficiently. In this vital study, authors have used descriptive statistics and multivariate regression model to determine the parameters. The findings show that the banks' internal factors have significant impact over its profitability with the exception of the liquidity variable and that external economic factors were insignificant at 5% confidence level. Hence, profitability in Afghan banks is determined by the efficiency of their management rather than macroeconomic factor of GDP. Keywords: Financial Performance, Commercial Banks, Afghanistan JEL Classification: G2